Demonstration of Cough Etiquette As an Effort to Reduce Pulmonary Tuberculosis Cases in Sindang Jaya Using a Community Diagnosis Approach - Natalia, Desi; Zahirah, Amirah Dea Putri; Widjaja, Evelin Maharani; Ernawati, Ernawati (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Pulmonary Tuberculosis is currently still a serious health problem and is very easily transmitted. Indonesia is the country with the second-highest number of new pulmonary TB cases in the world. The Tangerang District Health Service at the end of 2022 found the number of pulmonary TB cases was 8,941 cases. There was an increase of 60% in new cases of pulmonary TB in Sindang Jaya District within 3 months in 2023. It was necessary to determine which villages had the main problem of pulmonary TB. This study aims to know the causes and carry out interventions to reduce new cases of pulmonary TB. Activities are carried out with a community diagnosis approach. A situation analysis is carried out to determine the problem. Identify the cause of the problem using the Blum Paradigm. Prioritization of problems using the Delphi non-scoring technique. Fishbone diagram to determine the root cause of the problem. Intervention plan with log frame goals and plan of action. Intervention is carried out through a demonstration of cough etiquette. There has been an increase in the ability to practice cough etiquette to help reduce the number of new cases of pulmonary TB. It was proven that 50% of the counseling participants could understand and practice cough etiquette well. After taking a community diagnosis approach, the cause of the problem was found and intervention was carried out, so it is hoped that new cases of tuberculosis in the Sindang Jaya Health Center working area will decrease. Keywords: Tuberculosis, Community Diagnosis, Blum Paradigm, Fishbone Diagram